5-Formyltriazoles as Valuable Starting Materials for Unsymmetrically Substituted Bi-1,2,3-Triazoles - Vroemans, Robby; Horsten, Tomas; Van Espen, Maarten; Dehaen, Wim (Frontiers in Chemistry, 2020)
Herein, we present the first synthetic methodologies towards non-symmetrical 5,5’-C,C-linked bi-1,2,3-triazoles starting from 5-formyl-1,2,3-triazole via two related pathways. In a first reaction, 5-formyl-1,2,3-triazole is successfully reacted with a variety of nitroalkanes and organic azides in a one-pot three-component fashion resulting in tetra-ortho-substituted bi-1,2,3-triazoles. In the second, closely related reaction, 5-formyl-1,2,3-triazole is initially converted with nitromethane to the corresponding nitroalkene, and then subsequently oxidatively cyclized with a number of organic azides towards 4-nitro substituted non-symmetrical tetra-ortho-substituted 5,5’-bi-1,2,3-triazoles. The scope of both reactions and further post-functionalizations are examined, and the atropisomeric properties of the obtained bi-1,2,3-triazoles are evaluated.